Prevalence of sickness presenteeism and associated factors among primary school teachers in Gondar city, northwest Ethiopia - Mamaye, Yimer; Yenealem, Dawit Getachew; Fentanew, Molla; Abebaw, Tadiwos; Melaku, Christian; Bezie, Anmut Endalkachew; Abie, Alebachew Bitew; Tesfaye, Amensisa Hailu (Frontiers in Public Health, 2024)
Background Sickness presenteeism, the phenomenon of people going to work despite being ill, is an occupational and psychosocial condition that hurts both the health of workers and organizational productivity. It negatively affects health, increases health-related costs, and the risk of contagious diseases. Primary school teachers are particularly vulnerable to this problem, although little is known about its scope and associated factors. This study aimed to determine the prevalence and factors associated with sickness presenteeism among school teachers in Northwest Ethiopia. Methods An institution-based cross-sectional study was employed and the study period was from April 18 to May 18, 2023. A sample of 633 primary school teachers was recruited using two-stage stratified random sampling. Data were collected using structured self-administered questionnaires. Epi-data version 4.6 and STATA version 14 were used for data entry and analysis, respectively. Binary logistic regression analysis was used. A multivariable logistic regression model with an adjusted odds ratio was fitted for statistical significance. Results A total of 603 school teachers participated in this study, with a response rate of 95.26%. The overall prevalence of sickness presenteeism in the last 12 months was 54.7% (N = 330) [95% CI (50.9, 58.7)]. Private school teachers [AOR: 2.21, 95% CI (1.14, 4.28)], low supervisor support [AOR: 1.53, 95% CI (1.06, 2.20)], lack of staff replacement availability [AOR: 2.74, 95% CI (1.85, 4.06)], low colleague support [AOR: 2.17, 95% CI (1.40, 3.37)], unsuitable household conditions [AOR: 1.49, 95% CI (1.08, 2.34)], and strict attendance control [AOR: 2.54, 95% CI (1.67, 3.85)] were factors significantly associated with sickness presenteeism. Conclusion The prevalence of sickness presenteeism was relatively high among primary school teachers because of factors such as low support from supervisors and colleagues, strict attendance control, lack of staff replacement, unsuitable household conditions, and private school type. Strategies to promote teachers’ health include fostering a culture of support and collaboration among colleagues, recruiting adequate staff, and implementing liberal attendance policies.